1995
DOI: 10.1037/0278-7393.21.3.711
|View full text |Cite
|
Sign up to set email alerts
|

The mere exposure effect is based on implicit memory: Effects of stimulus type, encoding conditions, and number of exposures on recognition and affect judgments.

Abstract: Research by D. L. L. A. Cooper (e.g.. Schacter cl al.. 1990. 1991) has shown that certain variables can dissociate explicit and implicit memory on recognition and object decision tests. If the same type of implicit memory representation is used in the affective preference test as in the object decision test, similar dissociations should occur for recognition and affect judgments. In 3 experiments the authors found a number of dissociations. However, unlike previous research that found object decision priming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
105
4
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(123 citation statements)
references
References 23 publications
11
105
4
3
Order By: Relevance
“…Previous studies of normal participants showed a particularly robust mere exposure effect with these objects (e.g., Seamon et al, 1995;Willems & Van der Linden, 2006). During the various phases, each participant was presented with a different combination of 12 sets of 7 stimuli in order to counterbalance the stimuli for the studied/distracter sets and recognition/preference tasks but also for the Standard/Non-analytic/Analytic conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies of normal participants showed a particularly robust mere exposure effect with these objects (e.g., Seamon et al, 1995;Willems & Van der Linden, 2006). During the various phases, each participant was presented with a different combination of 12 sets of 7 stimuli in order to counterbalance the stimuli for the studied/distracter sets and recognition/preference tasks but also for the Standard/Non-analytic/Analytic conditions.…”
Section: Methodsmentioning
confidence: 99%
“…A wellestablished explanation of this implicit memory effect is that participants develop a preference bias because the prior encounter with a stimulus enhances its subsequent perceptual fluency (e.g., Bornstein & D'Agostino, 1994;Seamon, Brody, & Kauff, 1983a, 1983bWhittlesea, 1993;Whittlesea & Price, 2001). In light of this background, the mere exposure effect falls into the same broad implicit memory category as perceptual priming, that is, the facilitation of or bias in the processing of a stimulus as a function of a recent encounter with that stimulus (Butler & Berry, 2004;Seamon et al, 1995). To explain this kind of implicit-explicit dissociation, some authors have proposed that perceptual priming may be mediated by a memory system (e.g., perceptual representation system or procedural memory system) separate from the system that mediates explicit memory (e.g., episodic or declarative memory system) (Cohen & Squire, 1980;Graf & Schacter, 1985;Seamon et al, 1995;Squire, 1992;Tulving & Schacter, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, earlier findings showed that, even when a feeling of fluency might be expected, some fluently processed stimuli may continue to elicit an explicit preference, such as after an obvious supraliminal presentation phase, of the kind that has been used in some mere exposure paradigms (e.g., Seamon et al, 1995Seamon et al, , 1997. Consequently, the nature of the connection between ease of processing and explicit preference judgments and the importance of additional indirect factors such as expectations and attributions of perceived fluency seem to be complex.…”
Section: Introductionmentioning
confidence: 99%
“…First, Seamon et al (1995Seamon et al ( , 1997 have shown a significant mere exposure effect by using the same kind of unfamiliar three-dimensional objects with supraliminal presentation and incidental encoding. In addition, it has been shown that pictures with a high figure-ground contrast are perceived as clearer and easier to process than low-contrast ones (Checkosky & Whitlock, 1973;Whittlesea, Jacoby, & Girard, 1990).…”
Section: Introductionmentioning
confidence: 99%